2020
DOI: 10.1101/2020.12.10.20243857
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Health Outcomes in Copd Smokers Using Heated Tobacco Products: A 3-Year Follow-Up

Abstract: BackgroundGiven that many patients with chronic obstructive pulmonary disease (COPD) smoke despite their symptoms, it is important to understand the long term health impact of cigarette substitution with heated tobacco products (HTPs). We monitored health parameters for 3-years in COPD patients who substantially attenuated or ceased cigarette consumption after switching to HTPs.MethodsChanges in daily cigarette smoking, annualized disease exacerbations, lung function indices, patients reported outcomes (CAT sc… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…Of the two available studies into long-term health effects, one reported physiologically favourable outcomes (Polosa et al, 2021b) whilst the other did not (Loffredo et al, 2021). There are currently no studies on the potential risk of heated tobacco product use on development of any form of cancer and long-term epidemiological studies into this may be warranted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the two available studies into long-term health effects, one reported physiologically favourable outcomes (Polosa et al, 2021b) whilst the other did not (Loffredo et al, 2021). There are currently no studies on the potential risk of heated tobacco product use on development of any form of cancer and long-term epidemiological studies into this may be warranted.…”
Section: Discussionmentioning
confidence: 99%
“…In the second study, health parameters were monitored for a period of three years in Chronic Obstructive Pulmonary Disease (COPD) smoking patients who substantially attenuated or ceased conventional cigarette consumption after transitioning to heated tobacco products (Polosa et al, 2021b). Changes in daily cigarette consumption, annualised disease exacerbations, lung function indices, self-reported outcomes and 6-minute walk distance from baseline were measured in the COPD patients using heated tobacco products after 12, 24 and 36 months.…”
Section: Chronic Use Studies (>1 Month)mentioning
confidence: 99%
“…There were some positive effects among people who used THS in terms of conditions associated with metabolic syndrome, with the most significant improvement being related to blood pressure." 34 In Italy, a retrospective study by Polosa et al 35 looked at the effects of HNB product use on changes in COPD status between 2017 and 2020. Daily cigarette consumption, yearly exacerbation events, pulmonary function, patient-reported health outcomes, and the results of a 6-minute walk test (6MWT) test were measured in 19 adult smokers with COPD who reduced conventional smoking (dual users) or achieved abstinence by switching to heated tobacco products at months 0, 12, 24, and 36.…”
Section: Clinical Evidence Basementioning
confidence: 99%
“…HTP are presented as "modified risk" tobacco products because switching to HTP can potentially reduce deleterious health effects associated with CC use. In a recent study, changes in a daily cigarette smoking, annualized disease exacerbations, lung function indices, patient-reported CAT scores, and 6-Minute Walk Test were measured in 19 COPD patients using HTP at 12-, 24-, and 36-months and compared with a group of age-and sex-matched COPD patients who continued using CC [11]. Subjects using HTP had a substantial decrease in annualized COPD exacerbations within the group mean at baseline and three year follow-up.…”
Section: Introductionmentioning
confidence: 99%